PENDAMPINGAN DAN SOSIALISI BILIK BACA “1000 BUKU” GUNA MENINGKATKAN KEMAMPUAN LITERASI MASYARAKAT: PENDAMPINGAN DAN SOSIALISI BILIK BACA “1000 BUKU” GUNA MENINGKATKAN KEMAMPUAN LITERASI MASYARAKAT - Meita Larasati; Asih Miatun (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2019)
The purpose of the Community Service Activity (PKM) is to sociallize about the fuction of read booth “1000 Buku” as a school library in Kadiroma Village Sub-District of Wawewa Tengah District of Southwest Sumba, East Nusa Tenggara. The implementation of the PKM is also a real ongoing effort of the UHAMKA Faculty of Economics and Business (FEB) team to empowering and improving literatition and education in Sub-District Wawewa Tengah as the one of isolated region in Indonesia. Due to the geographical condition, this area is difficult to reached by the government and outside communities so that make the village backward. Therefore, to face the problem, the University of Muhammadiyah Prof Dr. HAMKA lecturer team took the initiative gave socialization about